2013
DOI: 10.1364/ol.38.000091
|View full text |Cite
|
Sign up to set email alerts
|

Random sources generating ring-shaped beams

Abstract: Two classes of scalar, stochastic sources are introduced, each capable of producing far fields with intensities forming rings. Although the Bessel-Gaussian and the Laguerre-Gaussian Schell-model sources are described by two different math models, the behavior of their degrees of coherence and, hence, the shapes of their far fields are qualitatively similar. The new beams are of importance for optical methods of particle manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(105 citation statements)
references
References 6 publications
3
102
0
Order By: Relevance
“…22,36 It is clear from the above expression that the source-plane spectral density S ¼ Wðq; qÞ is Gaussian. With the BGSM cross-spectral density W provided above, a closed-form expression for the far-zone W can easily be derived.…”
Section: Bessel-gaussian-correlated Schell-model (Bgsm) Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…22,36 It is clear from the above expression that the source-plane spectral density S ¼ Wðq; qÞ is Gaussian. With the BGSM cross-spectral density W provided above, a closed-form expression for the far-zone W can easily be derived.…”
Section: Bessel-gaussian-correlated Schell-model (Bgsm) Sourcementioning
confidence: 99%
“…With the BGSM cross-spectral density W provided above, a closed-form expression for the far-zone W can easily be derived. 22,36 In the experiments, the far-zone BGSM W is produced by using a lens, where the lens and source plane are collocated. This scenario is equivalent to the classic Fourier optics problem of an input placed against a lens.…”
Section: Bessel-gaussian-correlated Schell-model (Bgsm) Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Various partially coherent beams with prescribed correlation functions have been investigated in both theory and experiment since Gori and collaborators derived the sufficient condition for constructing the genuine correlation functions [2,3] . Recent studies have shown that specially correlated partially coherent beams display many unique but interesting properties, e.g., self-splitting effect appears in a Hermite-Gaussian correlated Schellmodel beam on propagation [9][10][11] , partially coherent beams with multi-Gaussian, Bessel-Gaussian and cosine-Gaussian correlated Schell-model functions exhibit prescribed farfield intensity distributions [12][13][14][15] , Laguerre-Gaussian correlated Schell-model beam produces an optical cage near the focal plane [16,17] . Due to those extraordinary properties, specially correlated partially coherent beams are useful in some applications, such as optical imaging, particle trapping, atom guiding and free-space optical communications.…”
Section: Introductionmentioning
confidence: 99%